ORGONOLEPTIC QUALITY AND YIELD OF FORTIFIED SHREDDED BALINESE DUCK WITH FERMENTED PINEAPPLE SKIN - U. N., Musalamah; Lindawati, S. A.; Miwada, I N. S. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the organoleptic quality and yield of fortified shreedded balinese duck with fermented pineapple peel. The study used a completely randomized design (CRD) with four treatments and four replications. The four treatments were: bali duck shredded without the fortified of pineapple peel as a control (P0), bali duck shredded with the fortified of 5% fermented pineapple peel (P1), bali duck shredded with the fortified of 10% fermented pineapple peel (P2), and bali duck shredded with the fortified of 15% fermented pineapple peel (P3). The variables observed were organoleptic quality including the hedonic preference (color, aroma, taste, texture, and overall acceptability) test and hedonic quality test (color, aroma, taste, and texture), and yield quality. The results showed that fortification of shredded balinese ducks with fermented pineapple peel had a significant (P<0.05) effect on color and yield, but had no significant effect (P>0.05) on aroma, taste, texture, and overall acceptability. From the results of this study it was concluded that the fortified of 15% fermented pineapple peel was the most preferred treatment by the panelists and shredded balinese ducks without the fortified of pineapple peel was the treatment with the highest yield value.